Endoscopic management of Lynch syndrome and of familial risk of colorectal cancer: European Society of Gastrointestinal Endoscopy (ESGE) Guideline - van Leerdam, Monique E.; Roos, Victorine H.; van Hooft, Jeanin E.; Balaguer, Francesc; Dekker, Evelien; Kaminski, Michal F.; Latchford, Andrew; Neumann, Helmut; Ricciardiello, Luigi; Rupińska, Maria; Saurin, Jean-Christophe; Tanis, Pieter J.; Wagner, Anja; Jover, Rodrigo; Pellisé, Maria (Endoscopy, 2019)
ESGE recommends that individuals with Lynch syndrome should be followed in dedicated units that practice monitoring of compliance and endoscopic performance measures.Strong recommendation, low quality evidence, level of agreement 100 %.ESGE recommends starting colonoscopy surveillance at the age of 25 years for MLH1 and MSH2 mutation carriers and at the age of 35 years for MSH6 and PMS2 mutation carriers.Strong recommendation, moderate quality evidence, level of agreement 100 %. ESGE recommends the routine use of high-definition endoscopy systems in individuals with Lynch syndrome. Strong recommendation, high quality evidence, level of agreement 100 %. ESGE suggests the use of chromoendoscopy may be of benefit in individuals with Lynch syndrome undergoing colonoscopy; however routine use must be balanced against costs, training, and practical considerations.Weak recommendation, moderate quality evidence, level of agreement 89 %.ESGE recommends definition of familial risk of colorectal cancer as the presence of at least two first-degree relatives with colorectal cancer or at least one first-degree relative with colorectal cancer before the age of 50 years.Strong recommendation, moderate quality evidence, level of agreement 92 %.ESGE recommends colonoscopy surveillance in first-degree relatives of colorectal cancer patients in families that fulfill the definition of familial risk of colorectal cancer.Strong recommendation, moderate quality evidence, level of agreement 100 %.